(untitled) (Journal of Partial Differential Equations, 2005)
In this paper, the local well posedness and global well posedness of solutions for the initial value problem (IVP) of nonlinear Schrödinger-Boussinesq equations is considered in H^s(R^d) by resorting Besov spaces, where real number s ≥ 0.